LAYANAN INFORMASI BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN SISWA EMPATIK SISWA SMP - Anggi Puji Utami; Edris Zamroni; Sucipto Sucipto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study stems from the importance of developing empathy in junior high school students as a foundation for prosocial character building and the prevention of negative behaviors such as bullying. Audio-visual media is considered capable of providing a more meaningful learning experience through a combination of verbal and visual messages that stimulate students' emotional involvement. This study aims to evaluate the effectiveness of audio-visual media-assisted information services in increasing the empathic attitudes of eighth-grade students at SMP 1 Karanganyar, Demak. The research subjects consisted of 30 eighth-grade E students selected using purposive sampling from a total population of 210 eighth-grade students. The research method used was a quasi-experiment with a pretest-posttest control group design. The data collection instrument was an empathy attitude scale that had been tested for validity and reliability (α = 0.87). The results of the data analysis showed that there was a significant difference between the pretest and posttest scores in the experimental group (t = 5.47; p < 0.05), while the control group did not show a significant difference. These findings indicate that audio-visual media-assisted information services are effective in increasing student empathy, with an average score increase of 12.87 points, which is much higher than the control group, which only increased by 1.40 points. The originality of this study lies in the application of audiovisual-based information services in the context of junior high schools with a rigorous quasi-experimental design, thus providing stronger empirical evidence than previous descriptive studies. The implications of this study encourage school counselors to integrate audio-visual media into guidance services, while further research is recommended to test the sustainability of the intervention effects through follow-up tests and expand the subjects in various educational contexts.